Analysis of Negotiation Text Writing Ability in Class X Students of SMA Nurul Iman Tanjung Morawa in the 2020/2021 Academic Year - Wisman Hadi; Sihombing, Herianto (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2022)
This study aims to describe the ability to write negotiating texts for tenth grade students of SMA Nurul Iman Tanjung Morawa. The population of this study was all students of class X SMA Nurul Iman Tanjung Morawa in the 2020/2021 academic year. The population of this study was all students of class X SMA Nurul Iman Tanjung Morawa in the 2020/2021 academic year which consisted of 10 classes with a total of 132 students. For this study, the sample taken was class X MIA-1, totaling 29 students through random sampling technique. This research uses descriptive analysis method. The data collection technique in this research is documentation. The research instrument used was a negotiating text writing test. The results showed that the ability of class X students of SMA Nurul Iman Tanjung Morawa in writing negotiating texts based on the structural aspect got an average score (93) in the very good category and the linguistic feature aspect got an average score (78.15) in the good category. . Based on the distribution table of the percentage value of the ability to write negotiating texts for class X students of SMA Nurul Iman Tanjung Morawa in; (1) the structural aspect shows the very good category (79.31%), good category (20.69%), quite good category (0%), and poor category (0%). (2) the aspect of linguistic characteristics shows in the very good category (31.04%), good category (51.72%), quite good category (17.24%), and poor category (0%). (3) the aspect of structure and linguistic characteristics shows in the very good category (34.48%), good category (58.62%), quite good category (6.89%), and poor category (0%). Indonesian language teachers can determine students' writing abilities, especially in writing negotiating texts based on structural aspects and aspects of linguistic characteristics. After knowing the students' abilities, the teacher can further improve the effectiveness of learning to write negotiating texts.